2023
DOI: 10.1002/mdc3.13729
|View full text |Cite
|
Sign up to set email alerts
|

10 Years Follow‐Up of Deep Brain Stimulation in the Caudal Zona Incerta/Posterior Subthalamic Area for Essential Tremor

Abstract: Background Long‐term data on the effects of deep brain stimulation (DBS) for essential tremor (ET) is scarce, especially regarding DBS in the caudal Zona incerta (cZi) and the posterior subthalamic area (PSA). Objectives The aim of this prospective study was to evaluate the effect of cZi/PSA DBS in ET at 10 years after surgery. Methods Thirty‐four patients were included. All patients received cZi/PSA DBS (5 bilateral/29 unilateral) and were evaluated at regular intervals using the essential tremor rating scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…We do not routinely target the cZI for SRS thalamotomy purposes. However, we recognize that DBS of the cZI or Vim ± cZI is now a well-acknowledged DBS target for drug-resistant ET [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…We do not routinely target the cZI for SRS thalamotomy purposes. However, we recognize that DBS of the cZI or Vim ± cZI is now a well-acknowledged DBS target for drug-resistant ET [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lesional PSA surgery is known to be effective for tremors in general and has been used in many rare tremor cases [14]. Open studies and two recent randomized blinded trials have suggested that DBS of the cZI/PSA is superior to VIM DBS in terms of tremor relief and current efficiency [4,24,43,45,62,63]. For rare tremor syndromes, the number of reports is very limited [5].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some recent research has suggested this to be a promising effective treatment [5,20,21]. However, there have not yet been any studies on double targeting of the VIM and PSA [22][23][24][25][26]. In the current study, we applied such double targeting to several rare tremor conditions to determine the efficacy and safety of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Other targets, such as the posterior subthalamic area and the caudal zona incerta, have also been investigated to manage the essential tremor motor symptoms. However, the data available for these targets are limited [51].…”
Section: Essential Tremormentioning
confidence: 99%